Challenges and drivers of green procurement among construction practitioners in Malaysia / Zafikha Aida Bidin ... [et al.] - Bidin, Zafikha Aida; Mohamad Bohari, Asmah Alia; Amat Rais, Syamimi Liyana; Mohamad Saferi, Munira; Olanipekun, Ayokunle (Universiti Teknologi MARA Cawangan Sarawak, 2020)
Construction is one of the sectors that contributes to a significant impact on the natural environment. There are many initiatives introduced to ensure that problems related to environmental degradation can be minimized. The introduction of green procurement is one of the strategies that helps in tackling issues related to the environment in the execution of construction projects in the Malaysian construction industry. However, knowledge of green procurement among construction stakeholders in Malaysia is still indicated as very low. Thus, the aim of this paper is to identify the driving factors in encouraging the inclusion of green practices in construction procurement. The findings of this paper provide the success factors identified from the literature review and focus group discussion. The outcome provides insights for construction practitioners to ensure green procurement in the delivery of construction projects